Предмет: Алгебра,
автор: katyaklimovich
(x+1):3-(x+2):6<(x+3):2
срочно с объяснением
Ответы
Автор ответа:
1
(х+1)/3-(х+2)/6<(х+3)/2
общий знаменатель 6
2(х+1)-(х+2)<3(х+3)
раскроем скобки
2х+2-х-2<3х+9
перенесём 3х+9 за знак < и приравняем нулю выражение
2х+2-х-2-3х-9=0
-2х-9=0
-2х=9
х=9:(-2)=-4.5
общий знаменатель 6
2(х+1)-(х+2)<3(х+3)
раскроем скобки
2х+2-х-2<3х+9
перенесём 3х+9 за знак < и приравняем нулю выражение
2х+2-х-2-3х-9=0
-2х-9=0
-2х=9
х=9:(-2)=-4.5
Похожие вопросы
Предмет: Математика,
автор: zlili7515
Предмет: Математика,
автор: Arbizik996
Предмет: Информатика,
автор: ASFADFAFAF
Предмет: Литература,
автор: hitomuy
Предмет: Математика,
автор: lovelylove1